Effective Management of Intellectual Capital and Organizational Performance on Selected Manufacturing Firms in Nigeria - Nneka, Maduagwu; Anthony, Kifordu A; Ann, Ogbo (International Research Journal of Management, IT & Social Sciences, 2016)
Intellectual capital is the deployment and management of intellectual capital resources and their transformations to maximize at present the organizations value creation in the eyes of its shareholders. Organizational performance is the extent to which the organizational objectives and goals are achieved in a competitive global business world. Most manufacturing firms fail in Nigeria because of inability to identify right caliber of workforce, know-how, relational management and lack of power sharing knowledge within and outside the operating environment. The objectives of this paper are: to ascertain the extent to which human capital development can be planned and harnessed to have differentiation advantage; explore the extent of relational capital can control low-cost provider advantage and determine the extent to which organizational capital can be designed most effectively in a competitive business world. Findings in line with the objectives revealed that human capital development promotes organizational synergy, motivation and understanding. Also that effectiveness of planning, control, performance measurement, profitability and future viability can be determined. A combination of the use of secondary data, oral interview and content analysis was adopted. Crombach Alpha reliability coefficient of 0.85 was obtained. Conclusion and recommendations was drawn along that direction.